The Anticipation of Crime and Corruption Problems Due to the Expansion of Telemedicine: A Study Based on the Korea Medical Crime Investigation System - Dongkyu, Lee (Frontiers in Public Health, 2021)
The telemedicine system, which has been gradually introduced, has changed dramatically with the outbreak of COVID-19. Now, with the development of related laws and technologies, the introduction of telemedicine will be further accelerated, and like the advent of smartphones, this will become an unstoppable trend of the times. However, just as there are various crimes and corruption problems in the current health system, the introduction of telemedicine may bring other problems. Therefore, it is important to anticipate the types of corruption or crimes that will occur with the introduction of telemedicine. And based on these expectations, we will have an opportunity to properly prepare for the various problems associated with telemedicine.